Women and youth of Wekweeti reveal the impacts of the diamond mines located in the Tlicho region. - Deegan, Victoria (Author); Schmidt, Glen (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2011)
This qualitative study was conducted as an attempt to better understand how the diamond mines in the Northwest Territories impact the remote Native community of Wekweètì socially, economically, and culturally. A blended methodology using participatory action and narrative approaches was used to strengthen rapport and work collaboratively with the community. The research participants were male and female youth between the ages of 12 and 24 and women 25 and older. Five talking circles, seven personal interviews, and the author's reflective journaling were three methods of collecting data. A thematic analysis identified nine main themes: Social impacts - Alcohol and Drugs, Parenting, and Jealousy Cultural impacts - Traditions Still Occurring, Traditions Occurring Less, and Loss of Language Economic impacts - Debt, Education/Training, and Standard of Living. The findings will be used to help the community advocate for social, economic and cultural services and supports from the diamond mines and various levels of government. --P. ii. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1741111